Left in limbo: patients' views on care across the primary/secondary interface. Issue 1 (1st March 1999) - Preston, C; Cheater, F; Baker, R; Hearnshaw, H
Abstract : OBJECTIVES: To discover the views of patients about their experiences across the interface between primary and secondary health care, including referral from general practitioners, outpatient and inpatient care, discharge, and aftercare. DESIGN: A qualitative study involving individual and focus group interviews of patients and interviews of carers. SUBJECTS: 33 patients who had attended at least one outpatient appointment or had been an inpatient between two and four months previously, and eight carers of patients with chronic conditions. SETTING: Three acute hospitals and one community health service in Leicestershire. MAIN OUTCOME MEASURES: Common themes in the views of patients and carers towards their experiences of care. RESULTS: Five themes emerged. The first four were: "getting in" (access to appropriate care), "fitting in" (orientation of care to the patient's requirements), "knowing what's going on" (provision of information), and "continuity" (continuity of staff and coordination and communication among professionals). The fifth theme was "limbo" (difficulty in making progress through the system), which was influenced by failures in care in relation to the other four themes. CONCLUSIONS: The concept of progress is central to patients' views of care. It involves both progress through the healthcare system and progress towards recovery or adjustment to an altered health state. Patients' views on how well they progress through the healthcare system may be an appropriate indicator for monitoring health service performance.